226k views
5 votes
Consider the system of equations below. What could be the first step in solving by elimination?

Consider the system of equations below. What could be the first step in solving by-example-1

2 Answers

2 votes

Answer:

The first step would be to multiply the bottom equation by -1 to eliminate x, then you would combine like terms, like 5y + 2y, and 16 + 10.

User Sleepsort
by
4.7k points
3 votes

Answer:

Subtracting the 2 equations

Explanation:

3x + 5y = 16

3x + 2y = 10

Subtract it;

3y = 6

Divide both sides b 3;

y = 2

Substitute y;

3x + 5y = 16

3x + 5(2) = 16

3x + 10 = 16

Subtract 10 from both sides;

3x = 6

Divide both sides by 3;

x = 2

(x, y) = (2, 2)

User Robert Fricke
by
4.9k points